GLP-1 receptorių agonistų vaidmuo sergant valgymo sutrikimais: apetito reguliavimas ir neurobiologiniai mechanizmai - Blažytė, Julija; Strumila, Robertas (Neurologijos seminarai, 2024)
Eating disorders, such as anorexia nervosa, bulimia nervosa, and binge eating disorder, are often linked to neurobiological dysfunctions, including alterations in dopamine and reward systems. Recent studies suggest that GLP-1 receptor agonists (GLP-1RAs) may have therapeutic effects not only on metabolic disorders but also on psychological conditions. GLP-1 regulates glucose metabolism, suppresses appetite, and influences dopamine signalling in reward pathways, potentially reducing binge eating episodes. Research indicates that GLP-1RAs may decrease stress-related eating by modulating the hypothalamic-pituitary-adrenal (HPA) axis and reducing anxiety-driven compulsive food intake. Clinical trials have shown that semaglutide and liraglutide effectively reduce binge-eating symptoms and cravings for high-calorie foods. The effects of GLP-1RAs on binge eating disorder appear to be more significant than those of traditional medications such as SSRIs, topiramate or lisdexamfetamine, though their long-term efficacy remains insufficiently studied. Despite promising results, GLP-1RAs may cause side effects, including gastrointestinal disturbances, hypoglycemia, and potential changes in mental health. Future research should assess their long-term impact and explore possible combinations with other treatment approaches, such as cognitive behavioural therapy.